2016
DOI: 10.2341/15-195-l
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Potential of Bulk Versus Incrementally Applied and Indirect Composites: Color, Microhardness, and Surface Deterioration

Abstract: This study investigated the color stability and microhardness of five composites exposed to four beverages with different pH values. Composite discs were produced (n=10); Filtek Z250 (3M ESPE) and Filtek P90 (3M ESPE) were applied in two layers (2 mm, 20 seconds), and Tetric N-Ceram Bulk Fill (TetricBF, Ivoclar Vivadent) and SonicFill (Kerr) were applied in bulk (4 mm) and then light cured (40 seconds, Ortholux-LED, 1600 mW/cm). Indirect composite Sinfony (3M ESPE) was applied in two layers (2 mm) and cured (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
5
26
0
2
Order By: Relevance
“…According to a study [ 29 ], bulk-fill composites had similar color stability to hybrid composite after 40 days of AAA, which is similar to Tiba and others [ 30 ], but in this study, after accelerated aging, both of the composites showed clinically noticeable color change and also bulk-fill composites became more colorful (2,92 NBS units) than anterior composites (2,40 NBS units) without fibers. This can arise from more than one factor.…”
Section: Discussionsupporting
confidence: 87%
“…According to a study [ 29 ], bulk-fill composites had similar color stability to hybrid composite after 40 days of AAA, which is similar to Tiba and others [ 30 ], but in this study, after accelerated aging, both of the composites showed clinically noticeable color change and also bulk-fill composites became more colorful (2,92 NBS units) than anterior composites (2,40 NBS units) without fibers. This can arise from more than one factor.…”
Section: Discussionsupporting
confidence: 87%
“…Both types of composites stained under the same condition, despite of the use of bulk fill resin composites in a single increment of 4 mm thickness. These results are in accordance with previous studies 2,16 , in which the bulk fill resin composites showed a similar color susceptibility when compared to conventional resin composites.…”
Section: Discussionsupporting
confidence: 93%
“…These resin composites were developed to allow bulk placement of increments up to 4 or 5 mm, skipping the time-consuming layering process 8 . There is limited information concerning the discoloration behavior of bulk fill resin composites, as well as the effect of the bleaching action on them 2,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the color stability of indirect composite commonly criticized as unpredictable and proved to be acceptable in several in vitro trials. [ 13 31 32 33 34 ]…”
Section: Discussionmentioning
confidence: 99%